Interpreting contemporary Christianity global processes and local identities - Kalu, Ogbu U. 1942-2009; Low, Alaine M. (Grand Rapids, Mich. ; Cambridge, U.K. Eerdmans, 2008)
Interpreting Contemporary Christianity is a multidisciplinary interpretation of world Christianity and the changing shape of the global religious landscape. The geographical coverage and the voices from various corners of the globe exemplify the impact of the shift of Christianity??`s center of gravity away from the northern hemisphere. New voices, new methods, and new perspectives emerge.
Includes bibliographical references and index
Archivierung prüfen
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Christianity; Konferenzschrift -- 2001 -- Pretoria; Aufsatzsammlung